Treatment of inguinal hernia with outpatient surgery - Nari, Gustavo; Oliva, Fernando; Prenna, Julio; Moreno, Eduardo; Olivares, Sergio (Cirugía del Uruguay, 1997)
There were studied 30 cases of reductible inguinal hernia using local anaesthesia far the surgical treatment, into an ambulatory surgery protocol. There were no technical inconvenients and patients had stayed at the Hospital only a few hours after the operation.